Procalcitonin for Diagnostics and Treatment Decisions in Pediatric Lower Respiratory Tract Infections - Baumann, Philipp; Baer, Gurli; Bonhoeffer, Jessica; Fuchs, Aline; Gotta, Verena; Heininger, Ulrich; Ritz, Nicole; Szinnai, Gabor; Bonhoeffer, Jan (Frontiers in Pediatrics, 2017)
Mortality and morbidity remain high in pediatric lower respiratory tract infections despite progress in research and implementation of global diagnostic and treatment strategies in the last decade. Still, 120 million annual episodes of pneumonia affect children younger than 5 years each year leading to 1.3 million fatalities with the major burden of disease carried by low and middle income countries (95%). The definition of pneumonia is still challenging. Traditional diagnostic measures (i.e. chest radiographs, C-reactive protein) are unable to distinguish viral and from bacterial etiology. As a result, common antibiotic overuse contributes to growing antibiotic resistance. We present an overview of current evidence from observational and randomized controlled trials on a procalcitonin-based diagnosis of pediatric lower respiratory tract infections and discuss the need for an adequate procalcitonin threshold for antibiotic treatment decision making.